2019
DOI: 10.1002/admi.201801842
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Wettability of Vertically Aligned CNT–TiO2 Hybrid Electrodes for Enhanced Supercapacitor Performance

Abstract: Boosting the energy density of carbon‐based materials is of great importance for developing supercapacitors with high cyclic stability. Chemical vapor deposition (CVD) growth of vertically aligned carbon nanotube (VACNT) forest is reported with millimeter height on Si/SiO2 substrate and engineer its microstructure and wettability for remarkable supercapacitor performance. A simple method to alter the microstructure of VACNT forest by adding small amount of ethanol in KOH electrolyte is demonstrated. The modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Other literature studies have also shown increased electrochemical performance because of increased wettability from the CNT composite, such as TiO 2 −CNT and polypyrrole-CNT. 29,30 Thus, the effect of the coating increasing wettability certainly contributes to the improved performance of the CoFe 2 O 4 -VACNT composite.…”
Section: Resultsmentioning
confidence: 99%
“…Other literature studies have also shown increased electrochemical performance because of increased wettability from the CNT composite, such as TiO 2 −CNT and polypyrrole-CNT. 29,30 Thus, the effect of the coating increasing wettability certainly contributes to the improved performance of the CoFe 2 O 4 -VACNT composite.…”
Section: Resultsmentioning
confidence: 99%
“…As is well documented in the literature, the wettability of the electrode surface directly influences the formation of the electrical double layer, and consequently, determines its capacitive charge storage capability. [20][21][22] Therefore, the superior performance of the FeS 2 SCs is probed by measuring the contact angles of the FeS 2 electrode with respect to TEABF 4 and EMIM-BF 4 electrolytes. Fig.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…[1] Based on the GCD curves, the areal capacitance of the hierarchical VACNTs electrode are calculated by formula (3) and the value is ≈1300 mF cm −2 , which is higher than most reported carbon-based SCs (Table 1). [13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] In addition, the specific capacitance can also be obtained by means of CV curve integration, namely Equation (4).…”
Section: Electrochemical Performance Of Hierarchical Vacnts-based Scmentioning
confidence: 99%